DJ-1 alleviates high glucose-induced podocyte injury via activating ERK1/2 signaling - Xiaochen Tian; Jing Li; Tao Han; Leisheng Zhang; Ping Lu; Yusheng Liu (PLoS ONE, 2026)
Diabetic nephropathy (DN) is a major diabetic complication, and while DJ-1 has been shown to mitigate renal ischemia/reperfusion injury, its role in high glucose-induced podocyte damage remains unclear. This study aimed to investigate the function and mechanism of DJ-1 in high glucose-induced injury of human podocyte cells (HPCs). Using RNA-seq analysis, we identified that high glucose broadly affected multiple signaling pathways related to cell growth, death, and signal transduction. Notably, DJ-1 expression was downregulated under high glucose conditions. Overexpression of DJ-1 significantly attenuated high glucose-induced HPC apoptosis. Mechanistically, DJ-1 promoted the phosphorylation of ERK1/2 and facilitated the nuclear translocation of p-ERK1/2. This activated the ERK1/2 pathway and upregulated the expression of NF-κB p65 and AP-1, thereby suppressing HPC apoptosis under high glucose conditions. In summary, our findings reveal that DJ-1 protects against high glucose-induced HPC injury by activating the ERK1/2 pathway and enhancing NF-κB p65 and AP-1 expression, providing new insights into the molecular mechanisms of DJ-1 in diabetic nephropathy.